Development of a technique to detect the presence of cow milk in goat milk: Development of a rapid test for detection of inter- species milk adulteration - Vandhana PS and Divya MP; Dr. Divya M P (Indian Journal of Dairy Science, 2024)
Adulteration of Goat milk in terms of mixing with Cow milk has emerged to be a serious issue in the recent years. The higher price and nutritional value coupled with limited availability of the former serves as the driving factor for the mixing of relatively cheaper, easily available cow milk to goat milk. The current available analytical techniques for the detection of presence of cow milk in goat milk are highly sophisticated, complex and time consuming which cannot be adopted at the basic level by private goat milk producers. So, the development of a simple rapid laboratory technique for the same which can be applied at the farm and society level is a need of the hour. This study was conducted using pure goat milk, pure cow milk and cow milk mixed with goat milk at different proportions of 25 percent, 50 percent and 75 percent. The physico chemical and compositional properties of samples were analysed and a significant variation between the samples was observed in terms of fat and chloride content. The ethanol stability was checked for the samples and found out that goat milk has lower ethanol stability compared to bovine milk and it improved by addition of cow milk. A blue colour which varies proportionately in intensity from light blue for pure goat milk to dark purple by increased addition of cow milk was observed by addition of Bromocresol purple and was verified using Hunterlab colorimeter. The addition of Seliwanoff’ s reagent to the above said samples led to the development of coagulum with significant differences in appearance such as a completely dispersed coagulum in case of goat milk and a clearly settled coagulum on top portion for cow milk. The rate of settlement of coagulum to the top increases with increase in content of cow milk in goat milk. The above stated differences may be considered as the basis for detection of presence of cow milk in goat milk. Further the Scanning Electron Microscopic study of coagulum was carried out and fatty acid profile of samples was analysed using GC-MS, which finally confirmed our results. This led to the development of a rapid test for detection of inter- species adulteration of goat milk with cow milk.Key words: Adulteration, Goat milk, Coagulum, Bromocresol purple, Seliwanoff’s reagent